From Stress to Wellbeing Volume 1 2013
DOI: 10.1057/9781137310651_10
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Work Demand Stressors and Job Performance: Examining Main and Moderating Effects

Abstract: We quantitatively integrated 169 samples (N = 35,265 employees) that have been used to investigate the relationships of the following 7 workrelated stressors with job performance: role ambiguity, role conflict, role overload, job insecurity, work-family conflict, environmental uncertainty, and situational constraints. Overall, we obtained a negative mean correlation between each job performance measure and each stressor included in our analyses. As hypothesized, role ambiguity and situational constraints were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
348
2
17

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(380 citation statements)
references
References 157 publications
13
348
2
17
Order By: Relevance
“…Early studies (e.g. Witt and Carlson 2006;Gilboa et al 2008;Karatepe 2008;Castanheira and Chambel 2010) found mixed results regarding the relationship between work-family conflict (both WIF and FIW) and job performance. Boles et al (2000), and Anderson et al (2002) found nonexistent and weak results between work-family conflict and job satisfaction.…”
Section: In Their Limitationmentioning
confidence: 99%
“…Early studies (e.g. Witt and Carlson 2006;Gilboa et al 2008;Karatepe 2008;Castanheira and Chambel 2010) found mixed results regarding the relationship between work-family conflict (both WIF and FIW) and job performance. Boles et al (2000), and Anderson et al (2002) found nonexistent and weak results between work-family conflict and job satisfaction.…”
Section: In Their Limitationmentioning
confidence: 99%
“…Operational failures occur in everyday work, particularly when the work is complex and requires inputs from more than one department within the organization, as is typical in healthcare (Beaudoin and Edgar 2003, Gurses and Carayon 2007, Hendrich et al 2008, Tucker 2004). Categories of operational failures include those related to information, tools and equipment, materials and supplies, budgetary support, help from others, and aspects of the work environment such as lighting (Gilboa et al 2008, Klein and Kim 1998, McNeese-Smith 2001, Peters and O'Connor 1980, Peters et al 1985, Villanova 1996.…”
Section: Prior Research On Operational Failures and Lean Manufacturinmentioning
confidence: 99%
“…Breaks help people recover physiologically from fatigue and thus serve a rejuvenating function (16,17). For instance, workers who stretch physically during short breaks from data entry tasks have been found to perform better than those who do not take breaks (16).…”
mentioning
confidence: 99%